(untitled) (Revista Apotheke, 2021)
In this article we propose to reflect on important aspects of the Art class in a formal or non-formal educational context - our focus is not on the relationship with institutions but with the epistemological issue of teaching. To begin with, we propose the differentiation between creativity and invention, political aspects of both concepts and because for us inventing is an act of emancipation of the subjects and creating, in the sense widely used in education, a concept co-opted by a market idea of education is configured. We analyzed the Art class and its relationship with the idea of relational or participatory art as we prefer. Finally, we think about the contributions that art can offer to education and its ways of doing, for that we envision education, in the broad sense, by the artistic paradigm and we seek to understand the fundamentals of education through the current scientific paradigm, that of the cognitive sciences